CAPITAL EMPLOYED EFFICIENCY DAN FAKTOR-FAKTOR PENENTU NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR INDONESIA - SUVI RATNA SARI; UMAR ISSA ZUBAIDI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
Research on the determinants of firm value has been widely conducted; however, empirical findings regarding the role of capital employed efficiency (CEE) remain inconclusive, particularly among manufacturing companies in Indonesia. In addition, studies that simultaneously examine CEE together with firms’ financial characteristics within a single empirical model are still relatively limited. Therefore, this study aims to investigate the effects of profitability, capital employed efficiency, firm size, asset growth, total asset turnover, leverage, and liquidity on firm value. The study employs 384 firm-year observations of manufacturing companies listed on the Indonesia Stock Exchange and applies multiple linear regression analysis. As an additional robustness assessment, White Heteroskedasticity-Consistent Standard Errors (HC3 Robust Standard Error) are employed to ensure the consistency of the estimation results in the presence of heteroskedasticity. The findings reveal that firm size and capital employed efficiency positively affect firm value, whereas total asset turnover has a negative effect. Meanwhile, profitability, asset growth, leverage, and liquidity do not significantly influence firm value. The robustness test confirms that the direction of the estimated relationships remains consistent with the main regression model, indicating that the findings are robust. These results highlight the importance of efficient capital utilization as a key determinant of firm value and provide practical implications for corporate management and investors in enhancing firm value through more efficient resource management.